Single cell RNA sequencing data from: Clonal competition within complex evolutionary hierarchies shapes AML over time. - Carl Sandén; Henrik Lilljebjörn; Christina Orsmark Pietras; Rasmus Henningsson; Karim H. Saba; Niklas Landberg; Hanna Thorsson; Sofia von Palffy; Pablo Peña-Martinez; Carl Högberg; Marianne Rissler; David Gisselsson; et al. (Lund University, 2020)
10x genomics single cell RNA sequencing data (fastq-files) from three samples representing one AML and two xenografted samples.
Keywords: Single cell RNA sequencing data; Medical and Health Sciences; Medicin och hälsovetenskap